Asymmetric labor markets and the location of firms: Are multinationals attracted to weak labor standards? - Alireza Naghavi (University College Dublin, Department of Economics, 2003)
This paper studies the strategic behavior of multinationals towards weak labor standards in developing countries (South). Without a marginal cost pricing policy, abundant labor in the South gives firms the power to set wages through their choice of output. A strategic reduction in output offsets or weakens direct gains from lower wages. In an open economy, it also increases output and profits of a competitor that operates in a perfect labor market. These effects lower profitability of locating in the South casting doubts on traditional beliefs that multinationals are always attracted to lower wages. Adopting standards enhances Southern welfare unambiguously.
hdl:10197/1787
Keywords: J80; F23; J42; F12; R38; L13; 330; Labor standards; Labor market imperfection; Oligopsony; Location of firms; Wages; Strategic behavior; Multinationals; Welfare